GENRE MODIFICATIONS OF THE HISTORICAL PROSE BY YURI MUSKETYKA - Beniuk, Kh. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
Historical fiction, continuing the main trends of the past and enriching with the experience of the present, received wide reader’s resonance and attracted the critics’ attention. That’s why the problem genre specific of historical novel and story upon on the materials of Ukrainian writer Yu. Mushketyk’s works on the historical theme is examined in the article.